2002
DOI: 10.1002/jcb.10182
|View full text |Cite
|
Sign up to set email alerts
|

Human cell DNA replication is mediated by a discrete multiprotein complex

Abstract: A discrete high molecular weight multiprotein complex containing DNA polymerase alpha has been identified by a native Western blotting technique. An enrichment of this complex was seen at each step in its purification. Further purification of this complex by ion-exchange chromatography indicates that the peak of DNA polymerase alpha activity co-purifies with the peak of in vitro SV40 DNA replication activity eluting from the column. The complex has a sedimentation coefficient of 18S in sucrose density gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
(76 reference statements)
0
22
0
Order By: Relevance
“…33,[35][36][37] These studies have shown that the replication activity present in a combined low-salt nuclear extract (NE)/ post mitochondrial cytosolic supernatant (S3), [NE/S3] partitions exclusively into the interface fraction (referred to as P4) after centrifugation on a 2M sucrose cushion. This procedure separates high molecular weight complexes that collect at the interface from soluble proteins in the supernatant fraction (designated S4) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33,[35][36][37] These studies have shown that the replication activity present in a combined low-salt nuclear extract (NE)/ post mitochondrial cytosolic supernatant (S3), [NE/S3] partitions exclusively into the interface fraction (referred to as P4) after centrifugation on a 2M sucrose cushion. This procedure separates high molecular weight complexes that collect at the interface from soluble proteins in the supernatant fraction (designated S4) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…39 It has been estimated that approximately 35 individual proteins make up this complex, which migrates as a single species on native polyacrylamide gels. 33,40 To determine whether DNMT1 is associated with the human cell DNA synthesome, the human breast cancer cell line MDA MB468 was fractionated as outlined in Figure 1, and the resulting purification fractions were analyzed for DNMT1 protein. Western blot analysis revealed that the 190kDa DNMT1 protein was present in the replication-competent NE/S3, P4, and Qs fractions from MDA MB468 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the critical regulatory points controlling human cell proliferation occurs at the level of DNA replication. Our laboratory successfully isolated, extensively purified, and characterized an intact mammalian cell multiprotein DNA-replication complex from a variety of human cell types that was both stable and fully functional (21)(22)(23)(24)(25)(26)(27)(28)(29). We proposed a model to represent the mammalian multiprotein DNA replication complex or DNA synthesome (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…N͞D, not determined. *The SV40 in vitro DNA replication assay was performed according to our procedures (21)(22)(23)(24)(25)(26)(27)(28)(29). † The DNA polymerase ␦ assay was performed according to the procedures of Han et al (35).…”
Section: Discussionmentioning
confidence: 99%